2004
DOI: 10.1063/1.1688317
|View full text |Cite
|
Sign up to set email alerts
|

Determining the adsorptive and catalytic properties of strained metal surfaces using adsorption-induced stress

Abstract: We demonstrate a model for determining the adsorptive and catalytic properties of strained metal surfaces based on linear elastic theory, using first-principles calculations of CO adsorption on Au and K surfaces and CO dissociation on Ru surface. The model involves a single calculation of the adsorption-induced surface stress on the unstrained metal surface, which determines quantitatively how adsorption energy changes with external strain. The model is generally applicable to both transition- and non-transiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 35 publications
0
21
1
Order By: Relevance
“…Extensive studies on surface stress induced by adsorbate interactions have been conducted by continuum approach, atomistic simulation and experiments (Kohn and Lau, 1976;Lau and Kohn, 1977;Berger et al, 1997;Pala and Liu, 2004). For example, Lau and Kohn (1977) investigated the indirect adsorbate interactions by treating an adsorbed atom as a force dipole on the surface of an unstrained half-space.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive studies on surface stress induced by adsorbate interactions have been conducted by continuum approach, atomistic simulation and experiments (Kohn and Lau, 1976;Lau and Kohn, 1977;Berger et al, 1997;Pala and Liu, 2004). For example, Lau and Kohn (1977) investigated the indirect adsorbate interactions by treating an adsorbed atom as a force dipole on the surface of an unstrained half-space.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Lau and Kohn (1977) investigated the indirect adsorbate interactions by treating an adsorbed atom as a force dipole on the surface of an unstrained half-space. Pala and Liu (2004) studied the effect of strain on the chemisorption energy based on the interaction energy between adsorbates and a solid surface. However, in these models, they only considered the indirect interactions between adsorbates mediated by the substrate and did not consider the direct adsorbate-adsorbate interactions.…”
Section: Introductionmentioning
confidence: 99%
“…(2) Relaxation of the surface stress upon hydroxylation due to the phenomena commonly known as adsorption induced stress (AIS). 23 (3) The bulk misfit-strain at large crystal size. Among three above mentioned factors, first two contribute toward the stability whereas the third one is a destabilizing factor.…”
Section: Introductionmentioning
confidence: 99%
“…Based on continuum theory, the relationship between adatoms and macroscopic stress was deduced [12]. With the linear elastic theory, Pala et al [13] demonstrated a model to determine the adsorptive and catalytic properties of strained metal surfaces. The solid surface is to some extent deformable, the surface bulges slightly towards the adsorbed molecule, but when the distances are closer the situation is reversed [14].…”
Section: Introductionmentioning
confidence: 99%